Play, development, and early education - Johnson, James E.; Christie, James F.; Wardle, Francis (Boston : Pearson A and B, 2005)
Play, Development, and Early Education challenges the reader to discover what play is and how to incorporate it into a curriculum for children from toddlerhood through the primary grades. The nature of play as a mode for learning is examined through three core ideas: the quality of play in early childhood, play as a means of self-expression, and play as a channel of communication to achieving social sense. In addition, the text addresses the role of parents in supporting and elaborating play, the direct connections between research and play practice, and the value of play in relation to the total development (cognitive, affective, emotional, social, and physical) of all children.
Includes bibliographical references and index.
Keywords: Play; Early childhood education; Child development